Effectiveness Curcuma Longa to Prevent Cells Damage in Early Pregnant Mice with Acute Toxoplasmosis - Tigor Peniel Simanjuntak; Mochammad Hatta; Syahrul Rauf; Andi Mardiah Tahir; Irawan Yusuf; Nurpudi Astuti Taslim; Robert Hotman Sirait; Silvia Arin Prabandari (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2019)
Objective: To prove the effectiveness of Curcuma longa to prevent damage cells by analyzing FOXP3 gene expression, TNF-α level, and histopathology of placental tissue. Method: This study was conducted in 20 early pregnant mice, divided in 5 groups (K1-K5). K1-K4 were injected with tachyzoites. K1 and K2 were intervened with Curcuma longa 125 and 500 mg/kg/day. K3 were intervened with spiramycin 60 mg/kg/day, K4 were intervened with 0,2 distilled water, and K5 was not injected and intervened. IgG-IgM levels, FOXP3 mRNA expression, TNF-α level was examined serially, and placental mice were taken for histopathology examination 7 days after intervention.Result: FOXP3 mRNA expression in K1 and K2 increased significantly 7 days after intervention compared to K4 (p < 0.05), however the increased of expression in two groups has no significant difference. TNF-α level in K1 and K2 decreased significantly 7 days after intervention compared to K4 (p < 0.05), however the decrease of level in two groups has no significant difference. Hemorrhagic and necrotic cells were not found in K1 and K2, but were found in K3 (75%) and K4 (100%). Conclusion: Curcuma longa 125 mg is effective to prevent cells damage in early pregnant mice with acute toxoplasmosis. Efektivitas Ekstrak Curcuma Longa Mencegah Kerusakan Sel Pada Mencit Hamil Muda dengan Toksoplasmosis Akut.AbstrakTujuan: Membuktikan efektivitas Curcuma longa mencegah kerusakan sel dengan menganalisis ekspresi gen FOXP3, kadar TNF-α, dan histopatologi jaringan plasenta.Metode: Penelitian dilakukan pada 20 tikus hamil muda, dibagi dalam 5 kelompok (K1-K5). K1-K4 diinjeksi 10 takizoid toksoplasma intra abdominal. Tiga hari pasca injeksi takizoid, K1 dan K2 diintervensi dengan Curcuma longa 125 dan 500 mg / kg / hari. K3 diintervensi dengan spiramisin 60 mg / kg / hari, K4 diintervensi dengan 0,2 ml air suling dan K5 tidak diinjeksi dan tidak diintervensi. Kadar IgG-IgM, ekspresi mRNA FOXP3, kadar TNF-α diperiksa secara serial dan plasenta tikus diambil untuk pemeriksaan histopatologi 7 hari pasca intervensi.Hasil: Ekspresi mRNA FOXP3 pada K1 dan K2 meningkat bermakna (p< 0.05) 7 hari pasca intervensi dibandingkan dengan K4 (p <0,05), tetapi peningkatan ekspresi pada kedua kelompok tidak terdapat perbedaan bermakna. Kadar TNF-α pada K1 dan K2 menurun bermakna 7 hari pasca intervensi dibandingkan dengan K4 (p <0,05), tetapi penurunan kadar pada dua kelompok tidak terdapat perbedaan bermakna. Hemoragik dan nekrotik sel tidak ditemukan pada K1 dan K2, tetapi ditemukan pada K3 (75%) dan K4 (100%).Kesimpulan: Curcuma longa 125 mg efektif untuk mencegah kerusakan sel pada tikus hamil muda dengan toksoplasmosis akut.Key words: Curcuma longa, kerusakan sel, hamil muda, gene FOXP3, TNF-α, toxoplasmosis